2010
DOI: 10.1002/jctb.2362
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction studies of Sm(III) from nitrate medium and separation factors of rare earth elements with mixtures of sec‐octylphenoxyacetic acid and 1,10‐phenthroline

Abstract: BACKGROUND: Liquid-liquid extraction is widely used for the separation of rare earths, among which synergistic extraction has attracted more and more attention. Numerous types of synergistic extraction systems have been applied to rare earths with high extraction efficiency and selectivities. In the present study, mixtures of sec-octylphenoxyacetic acid (CA12, H 2 A 2 ) and 1,10-phenanthroline (phen, B) have been used for the extraction of rare earths from nitrate medium. The stoichiometry of samarium(III) ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Besides precipitation, several studies on solvent extraction as an effective route for separation of Sm were reported. Processing of a SmCo magnet for recovery of Sm and Co, and separation of Sm using CYANEX 572 from chloride leach liquor, was reported . The authors demagnetized the waste magnet by roasting at 1123 K prior to leaching with 4 M HCl at 368 K under 100 g/L S:L. Precipitated Sm and Co oxalates were calcined to produce oxides of Sm and Co.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides precipitation, several studies on solvent extraction as an effective route for separation of Sm were reported. Processing of a SmCo magnet for recovery of Sm and Co, and separation of Sm using CYANEX 572 from chloride leach liquor, was reported . The authors demagnetized the waste magnet by roasting at 1123 K prior to leaching with 4 M HCl at 368 K under 100 g/L S:L. Precipitated Sm and Co oxalates were calcined to produce oxides of Sm and Co.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of D2EHPA to the CYANEX 301 extraction system increased the extraction efficiency of CYANEX 301 with better stripping in the low concentration range. In another study, a mixture of sec-octylphenoxyacetic acid and 1,10-phenthroline was used for extraction of Sm and other REEs from a synthetic solution in nitrate medium . A comparative study on separation of Co (II) and Sm (III) by dissolving their chloride salts in water as well as in ethylene glycol (EG) in the presence of LiCl was studied .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent decades, synergistic extraction systems have been applied many times to the separation of REEs. Various mixtures of two extractants have been investigated for the extraction of REEs, including carboxylic acids,1, 5, 7–18 acidic organophosphorous extractants,19–21 neutral organophosphorous extractants,22–24 crown ethers,25, 26 and amines (ammonium salts) 27. Among these reagents, CA100 has been proved to be an excellent synergistic extractant.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of mixed ligand chelates involving the chelating extractants and various adducts not only provide better extractability, but also improve separation. The extraction of REEs from acidic nitric solutions with binary mixtures of 1, 10‐phenanthroline (phen) with sec ‐octylphenoxyacetic acid (CA12) and CA100 have been studied in the laboratory 7, 16. 2,2′‐bipyridyl (bipy) has a similar structure to phen, and has also proven to be an excellent synergistic.…”
Section: Introductionmentioning
confidence: 99%